"I Like English Better": Latino Dual Language Students' Investment in Spanish, English, and Bilingualism. Issue 1 (2nd January 2017) - Babino, Alexandra; Stewart, Mary Amanda
ABSTRACT: This mixed-methodology study surveys 63 fifth graders in a one-way dual language school. Findings alarmingly indicate that although these students are native Spanish speakers in a school that delivers 50% of their instruction in Spanish, they prefer English both academically and socially. Subsequent interviews with 10 sample students of the larger study generate deeper understandings about how these students view their languages. If dual language programs are going to be maximally successful, then they must foster an environment that encourages students' attitudes and investments toward both of their languages, taking particular care to protect and promote the minority language.